Stabilisation of PFAS in soils: Long-term effectiveness of carbon-based soil amendments. (15th April 2023) - Navarro, Divina A.; Kabiri, Shervin; Ho, Jonathan; Bowles, Karl C.; Davis, Greg; McLaughlin, Mike J.; Kookana, Rai S.
Abstract: Immobilisation/stabilisation is one of the most developed and studied approaches for treating soils contaminated with per- and poly-fluoroalkyl substances (PFAS). However, its application has been inhibited by insufficient understanding of the effectiveness of added soil sorbents over time. Herein, we present results on the effectiveness of select carbon-based sorbents, over 4 years (longevity) and multiple laboratory leaching conditions (durability). Standard batch leaching tests simulating aggressive, worst-case scenario conditions for leaching (i.e., shaking for 24–48 h at high liquid/solid ratios) were employed to test longevity and durability of stabilisation in clay-loam and sandy-loam soils historically contaminated with PFAS (2 and 14 mg/kg ∑28 PFAS). The different sorbents, which were applied at 1–6% (w/w), reduced leaching of PFAS from the soils to varying degrees. Among the 5 sorbents tested, initial assessments completed 1 week after treatment revealed that 2 powdered activated carbon (PAC) sorbents and 1 biochar were able to reduce leaching of PFAS in the soil by at least 95%. Four years after treatment, the performance of the PAC sorbents did not significantly change, whilst colloidal AC improved and was able to reduce leaching of PFAS by at least 94%. The AC-treated soils also appeared to be durable and achieved at least 95% reduction in PFAS leaching under repetitive leaching events (5 times extraction) and with minimal effect of pH (pH 4–10.5). In contrast, the biochars were affected by aging and were at least 22% less effective in reducing PFAS leaching across a range of leaching conditions. Sorbent performance was generally consistent with the sorbent's physical and chemical characteristics. Overall, the AC sorbents used in this study appeared to be better than the biochars in stabilising PFAS in the long term. Graphical abstract: Image 1 Highlights: Efficacy of soil stabilisation treatments may change over time. Activated carbon can reduce leaching of PFAS in both short and long term. Biochars in this study were only effective in the short term. Sorption of PFAS onto AC is predominately driven by hydrophobic interactions. Sorbent performance was consistent with the sorbent's physico-chemical properties.